Midbrain Atrophy in Vascular Parkinsonism - Choi, Seong-Min (S. Karger AG, 2011)
BACKGROUND: Midbrain atrophy is a well-known feature of progressive supranuclear palsy (PSP). Some clinical features of vascular parkinsonism (VP) such as pseudobulbar phenomena, lower body predominance and early postural instability suggest that the brainstem could be associated with VP. The aim of this study was to determine whether midbrain atrophy was present in patients with VP. METHODS: We measured the midbrain (Amd) and pons area (Apn) of 20 patients with VP, 15 patients with probable PSP and 30 patients with idiopathic Parkinson's disease (IPD). The Amd and Apn were measured on mid-sagittal T(1)-weighted MRI scans using a computerized image analysis system. RESULTS: For the Amd, the patients with VP (99.86 mm(2)) and PSP (87.30 mm(2)) had significantly smaller areas than the patients with IPD (130.52 mm(2)). For the Apn, there was a significant difference only between the VP (407.23 mm(2)) and the IPD (445.05 mm(2)) patients. The Amd/Apn ratios of the patients with VP (0.245) and PSP (0.208) were significantly smaller than in the patients with IPD (0.292). CONCLUSIONS: Our study shows that brainstem atrophy often occurs in patients with VP and the midbrain is more vulnerable than the pons to atrophic changes.